Aneurysm in the Distal Portion of the Extern Jugular Vein in a Horse - Santos, Alice Correa; Pazinato, Fernanda Maria; Vieira, Patrícia Soares; de Araújo, Luciana Oliveira; de Oliveira, Laura Corrêa; Raffi, Margarida Buss; Curcio, Bruna da Rosa; Nogueira, Carlos Eduardo Wayne (Acta Scientiae Veterinariae, 2016)
Background: Aneurysm is a vascular disease that causes the partial rupture of arteries and veins and subsequent blood leakage due to the weakening of the vessels elastic middle layer. Venous aneurysms in horses are rare, but the arterial aneurysms are commonly reported. The aim of this paper is to report a rare occurrence of jugular external aneurysm in a horse and propose the inclusion this disease as a differential diagnosis, both because it is rare in this specie and invariably fatal. The medical examination showed a firm well-defined mass, painless, nonpulsatile on palpation and with no changed in the local temperature. Case: The horse was referred to the Veterinarian Hospital of the Federal University of Pelotas (UFPel, RS-Brazil. It was a male, Crioulo breed, 10 years old, used as stallion. The owner reported a swelling in the pectoral region that occurred after a trauma episode that had gradually grown for two years. The patient was clinically stable, and would undergo surgery extirpation for aesthetic matters. Clinical examination showed the swelling was circumscribed and centralized and it presented about 20 centimeters in diameter. The ultrasound of the pectoral area showed an anechoic structure with hyperechoic spots inside limited by an hyperechoic layer similar to a fibrous capsule. Presumptive diagnostics were of: hematoma, subcutaneous abscess, neoplasia, and possible vascular involvement. The use of conventional ultrasound was not enough to set the diagnosis, and the patient was referred to surgical exploration, where the procedures of isolation and anastomosis were performed, however rupture occurred and the patient died. Necropsy revealed sacculation of the ventral region of the neck next to the entrance of the thorax, and the involvement of the external right jugular vein, being the adjacent muscle tissue not involved. Histopathological evaluation showed intense proliferation of sub-endothelial fibrous tissue which infiltrated the tunica media and adventitia and a mild inflammatory infiltrate of lymphocytes and histiocytes, which was diagnosed as an aneurysm of the right external jugular vein. Discussion: The reported patient had a venous aneurysm located superficially, which may have contributed to the absence of symptoms. The ultrasound is a diagnostic method available to most veterinarians nowadays, mainly in the countryside. However, when it is used in the diagnosis of an aneurysm it displays a dilatation with anechoic content, which is common to several other skin diseases. A similar ultrasound image was observed in the case reported, but the diagnosis was difficult because the aneurysm presented intense proliferation of fibrous tissue infiltrated in the media and adventitia of the vascular wall, similar to a capsule of fibrous tissue, which lead to the presumptive diagnostics of hematoma, abscess and neoplasia, with possible vascular involvement. The options for the treatment of the aneurysms consider the location, size and extent of them and it determines the choice between clinical observation and surgery. In veterinary medicine it is difficult to keep the animals still and in the case of a horse, any movement can lead to the spontaneous rupture of the aneurism. Considering the risk of spontaneous rupture and hemorrhage, the surgical resolution, even if risky, emerges as the most suitable treatment. Venous aneurysms although rare, need to be included as a differential diagnosis in skin diseases along with increased volume, as hematomas, abscesses and tumors. The prognosis, however, is poor because of the surgical limitations and risks of imminent rupture in the clinical treatment. Keywords: venous aneurysm, differential diagnosis, equine.